Study of High Yielding Varieties Programme - Planning Commission (Planning Commission, 1967)
For the studies undertaken by the P.E.O. during the year 1966, methodological papers on the background of the study, objectives, scope, sampling method, schedules and instructions thereon, were brought into a compendium for the convenience of the investigating officers. This was greatly appreciated by the field staff. The same procedure is followed in the case of the studies proposed for this year also This brochure is the result of the joint efforts of all the officers of the P.E.O., specially of those of the Agricultural Economics Division.
Design, Schedule, Etc. and Instructions Programme Evaluation Organisation Planning Commission Government of India